A critical assessment of the ideological underpinnings of current practice in global health and their historical origins. Issue 1 (1st January 2019) - Kim, Hani; Novakovic, Uros; Muntaner, Carles; Hawkes, Michael T.
ABSTRACT: Background : The current approach to global health has significantly contributed to improving it, as evidenced by the progress made toward the Millennium Development Goals (MDGs). However, the health gains achieved are often highly unequitable, and the current approach is expected to be insufficient to meet the future health equity challenges. There is an urgent need to re-think and expand the scope of research and programmatic strategies. Objective : This paper aims to assess the ideological underpinnings of the currently dominant norms in global health, with the goal of highlighting the research and programmatic areas that are marginalized and warrant greater efforts in order to resolve persistent health inequity and achieve the UN Sustainable Development Goals (SDGs). Methods : We have conducted a critical review of the literature that traces the historical origins of global health to the period between the mid-19th century and the end of the 20th century. Results : Critical review of the historical origins of global health reveals a set of dominant norms in global health that are ideological in character, and profoundly shape the current practice. We identified key manifestations of the ideological underpinnings as 1) Democratic deficit, 2) Depoliticization of the discourse, 3) Marginalization of the scholarship that interrogates the relations of power. Conclusion : Examination of the dominant norms that shape the foundation of our knowledge and action in global health is required to solve persistent health inequity challenges and meet the SDGs. Inversion of the key manifestations of the dominant norms can serve as guiding principles to elaborate alternative frameworks that have the theoretical and programmatic potential for a fundamental rather than an incremental change in the practice of global health.